Effect of acid activation on the mechanical and shrinkage properties of cement-based materials. (1st June 2023) - Xu, Zhishan; Ji, Yongsheng; Zhao, Yanpeng; Xu, Shengnan; Zhang, Zhongzhe; Gao, Furong; Zhang, Jie; Xue, Qi; Song, Menglong
Abstract: Effect of acid activation on compressive strength, shrinkage, microstructure and hydration process of cement-based materials is studied by adding acid activator to them. The strengthening mechanism of acid activation on the mechanical properties and shrinkage resistance of cement-based materials is proposed based on the effects of acid on cement particles, fresh paste and hardened paste, combined with multi-level analysis by microscopic means. The results show that acid activation can significantly improve the compressive strength and shrinkage resistance of cement-based materials. The reason for this is that the acid activator has the effect of refining cement particles, increasing the particle concentration of fresh paste, and densifying hardened paste microstructure. Highlights: Acid activation can greatly improve the compressive strength of cement-based materials. Acid activation can significantly inhibit the shrinkage of cement-based materials. The acid corrosion has the effect of refining the cement particle size. The acid significantly improves the concentration of particles in the cement paste. Acid has the effect of optimizing the pore structure of cement-based materials.